2021
DOI: 10.1159/000517531
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of a Real-World Patient Cohort with Secondary CNS Lymphoma Treated with High-Intensity Chemoimmunotherapy and Autologous Stem Cell Transplantation

Abstract: <b><i>Background:</i></b> Aggressive non-Hodgkin lymphomas with secondary central nervous system (CNS) involvement bear a dismal prognosis. Optimal treatment remains so far unclear, and effective treatment options remain an unmet clinical need. Remission rates are in general low, resulting in rapid relapses and palliative care in the majority of patients. High-intensity treatment combining effective CNS-directed chemoimmunotherapy with autologous stem cell transplantation was shown in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Less data is presented for prior hematologic/lymphatic cancers. One retrospective cohort study of patients with non‐Hodgkin lymphoma and second primary CNS involvement found a median survival time of 11 months, which differs from the 7 months found here 28 . These findings contextualize the importance of inclusion of patients with second primary brain cancer in ongoing clinical trials.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Less data is presented for prior hematologic/lymphatic cancers. One retrospective cohort study of patients with non‐Hodgkin lymphoma and second primary CNS involvement found a median survival time of 11 months, which differs from the 7 months found here 28 . These findings contextualize the importance of inclusion of patients with second primary brain cancer in ongoing clinical trials.…”
Section: Discussionsupporting
confidence: 51%
“…One retrospective cohort study of patients with non-Hodgkin lymphoma and second primary CNS involvement found a median survival time of 11 months, which differs from the 7 months found here. 28 These findings contextualize the importance of inclusion of patients with second primary brain cancer in ongoing clinical trials. In an analysis of 464 clinical trials, more than one-third excluded this population completely, with another one-third instituting conditional exclusion criteria.…”
Section: Discussionmentioning
confidence: 83%
“…Table 2 shows the results of clinical trials and retrospective studies that included patients with systemic DLBCL or HGBL with synchronous CNS involvement at diagnosis (studies with ⩽15 patients with synchronous CNS involvement at diagnosis were not included). 14,[20][21][22][23][24] The table highlights the paucity of published data and considerable heterogeneity in patients' characteristics and types of treatments received. Furthermore, none of these studies reported on the outcomes of patients with HGBL specifically.…”
Section: Outcomes Based On Receipt Of Hctmentioning
confidence: 99%
“…However, there are no such data for patients with secondary CNSL. Only few reports support the use of analogous treatment strategies in secondary CNSL, but the feasibility of HDT/ASCT is limited for these patients due to failure of salvage treatment, toxicity and unsuccessful stem cell harvest (7,8).…”
Section: Introductionmentioning
confidence: 99%